The impact of institutional formation on firms’ strategic choices in knowledge development, absorptive capacity and vertical integration - Ray, Pradeep Kanta; Klarin, Anton; Ray, Sangeeta (Springer Nature, 2022)
This study examines the impact of institutional shifts on the strategic choices of Russian firms. It proposes and tests hypotheses of how a shift from a weak to a strong institutional context is likely to affect firms’ knowledge accumulation, absorptive capacities and internalisation of operations. Using discriminant analysis, the econometric investigation demonstrates that firms tend to allocate greater resources towards improving their knowledge and absorptive capacity and make more efforts to vertically integrate—in line with improvements in the institutional environment. These investments ensure the survivability and competitiveness of firms in the long term. Furthermore, the study demonstrates that the long-term strategic orientation of firms goes hand in hand with rising resource allocations by the nation-state towards economic development. The findings align with the institutionalist political economy views that institutions are the ultimate overseers that allow the market to operate efficiently, especially in emerging market environments. The paper is also instructive to other developing economies about the need to strengthen their institutional environments, which supports the long-term orientation of firms and has a positive impact on economic development. The analysis does not take into account the impact of sanctions on Russian business and economy, post the annexation of Crimea and the armed conflict with Ukraine. Nor does it consider the impact of COVID-19 on the economy. As such, the study attempts to constitute an untainted comparison of two paths of transition on Russian firms—shock therapy, vis-à-vis, an institutional political economy approach.